Does adjuvant therapy improve overall survival for stage IA/B pancreatic adenocarcinoma?. Issue 7 (July 2017) - Ostapoff, Katherine T.; Gabriel, Emmanuel; Attwood, Kristopher; Kuvshinoff, Boris W.; Nurkin, Steven J.; Hochwald, Steven N.
Abstract: Background: Current guidelines recommend adjuvant chemotherapy for resected pancreatic adenocarcinoma (PDAC). However, no studies have addressed its survival benefit for stage I patients as they comprise <10% of PDAC. Methods: Using the NCDB 2006–2012, resected PDAC patients with stage I disease who received adjuvant therapy (chemotherapy or chemoradiation) were analyzed. Factors associated with overall survival (OS) were identified. Results: 3909 patients with resected stage IA or IB PDAC were identified. Median OS was 60.3 months (mo) for stage IA and 36.9 mo for IB. 45.5% received adjuvant chemotherapy; 19.9% received adjuvant chemoradiation. There was OS benefit for both stage IA/IB patients with adjuvant chemotherapy (HR = 0.73 and 0.76 for IA and IB, respectively, p = 0.002 and <0.001). For patients with Stage IA disease (n = 1, 477, 37.8%), age ≥70 (p < 0.001), higher grade (p < 0.001), ≤10 lymph nodes examined (p = 0.008), positive margins (p < 0.001), and receipt of adjuvant chemoradiation (p = 0.002) were associated with worse OS. For stage IB patients (n = 2, 432, 62.2%), similar associations were observed with the exception of adjuvant chemoradiation whereby there was no significant association (p = 0.35). Conclusion: Adjuvant chemotherapy was associated with an OS benefit for patients with stage I PDAC; adjuvant chemoradiation was either of no benefit or associated with worse OS.